KEY ASPECTS OF THE THEORY OF DIGITAL TRANSFORMATION OF BUSINESS PROCESSES - Azamat Davletyarov; Dilmurod Suyunov; Aman Kenzhabaev (American Journals, 2023)
In the article and study the methodological aspects of the digital transformation of business processes of enterprises. The analysis of foreign experience in the methodology of digital transformation of business processes of organizations was carried out. Proposals and recommendations for the methodology of digital transformation of business processes have been developed.
Keywords: digitalization of business, digital process, digitalization of enterprises, digital technologies.